2022
DOI: 10.1001/jamaneurol.2022.0976
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Alzheimer Disease and Related Dementias by Sex and Race and Ethnicity in the US

Abstract: IMPORTANCE Previous estimates suggested that 1 in 3 cases of Alzheimer disease and related dementia (ADRDs) in the US are associated with modifiable risk factors, the most prominent being physical inactivity, depression, and smoking. However, these estimates do not account for changes in risk factor prevalence over the past decade and do not consider potential differences by sex or race and ethnicity.OBJECTIVE To update estimates of the proportion of ADRDs in the US that are associated with modifiable risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…The relationship of BMI with cognitive function has been reported in numerous studies with inconsistent findings. Some studies found neuroprotective effects for the BMI-defined statuses of overweight and obese in later life [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], while some research reported detrimental neurological effects caused by BMI-defined obesity [ 6 , 9 , 10 , 11 , 12 ]. We found that a reverse J-shaped relationship of BMI with cognitive impairment was identified in the current research, suggesting that the BMI-defined statuses of overweight and obese could be related to a decreased risk of cognitive impairment and that the BMI-defined status of underweight could be related to an increased risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of BMI with cognitive function has been reported in numerous studies with inconsistent findings. Some studies found neuroprotective effects for the BMI-defined statuses of overweight and obese in later life [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], while some research reported detrimental neurological effects caused by BMI-defined obesity [ 6 , 9 , 10 , 11 , 12 ]. We found that a reverse J-shaped relationship of BMI with cognitive impairment was identified in the current research, suggesting that the BMI-defined statuses of overweight and obese could be related to a decreased risk of cognitive impairment and that the BMI-defined status of underweight could be related to an increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism has not been completely explained, it has been widely proposed that unfavorable weight status may affect metabolic functions, promote inflammation, and disrupt the balance of gut microbiota, which could increase the risk of poor cognitive function [ 5 ]. However, previous epidemiological studies have shown conflicting results between BMI and cognitive function, with some research suggesting that higher BMI contributes to poor cognitive function [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], and other studies observing an apparent beneficial effect of higher BMI on cognitive function [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Also, few large, prospective cohort studies have been conducted in the older Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to generally having more pre-dispositional factors, it is important to note that women also have a higher rate of mortality due to obesity-related complications because they have a higher risk of developing these complications [ 27 ]. Dementia is one such complication, and given that JAMA reports that two-thirds of the adults diagnosed with AD are women, obesity is a pivotal modifiable risk factor [ 5 ].…”
Section: Factors Affecting the Development Of Obesitymentioning
confidence: 99%
“…Current research links the obesity epidemic to multiple detrimental chronic conditions (e.g., diabetes, heart disease, dementia) that have lowered the quality and length of life for countless individuals ( Figure 1 ) [ 3 ]. As of 2020, 55 million people have been diagnosed with dementia and by 2050 this number is expected to rise to 139 million, likely due to the steady rise in obesity prevalence [ 3 , 4 , 5 ]. This article examines the factors surrounding the development of obesity and the role that obesity plays in perpetuating the prevalence of diabetes and dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation